2012
DOI: 10.1007/bf03262874
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Pre-eruptive intra-coronal radiolucencies revisited

Abstract: Early detection and classification of the PEIR lesion allows an array of individualised treatments to be provided for successful outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 13 publications
2
48
0
11
Order By: Relevance
“…11,15 In contrast to our case, Holan et al found yellowishbrown soft tissue in the resorptive area of the tooth in their first case, but their second case had yellowwhite soft tissue similar to our case. 4 Any systemic disturbance or local trauma that injures the odontoblasts during dentin formation can cause an interruption or an arrest in matrix apposition, which results in hypoplasia.…”
Section: Discussionsupporting
confidence: 50%
“…11,15 In contrast to our case, Holan et al found yellowishbrown soft tissue in the resorptive area of the tooth in their first case, but their second case had yellowwhite soft tissue similar to our case. 4 Any systemic disturbance or local trauma that injures the odontoblasts during dentin formation can cause an interruption or an arrest in matrix apposition, which results in hypoplasia.…”
Section: Discussionsupporting
confidence: 50%
“…Treatments such as pulp protection or pulpectomy are performed in cases in which the pulp is affected. In the literature there are reports of rare cases in which the lesion progressed rapidly, and extraction of the tooth was indicated [1][2][4][5][6][7]10 .…”
Section: Discussionmentioning
confidence: 99%
“…This lesion is generally localized on the occlusal, distal or mesial surfaces of the coronal portion, extending into various depths of dentin, rarely involves the pulp and preserves the healthy crown [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . It may be confused with caries, and mistakenly The best treatment option in this case was followup to minimize the risk of caries, and obtain stabilization of the lesion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations